"I'm the Mang!": Latino authenticity and subversion in the boxing ring. Issue 4 (December 2016) - Zavala, Noel
Abstract This article demonstrates how the act of "coming out" can work to subvert hegemonic notions of "authentic" Latino male masculinity. I posit that Latino authenticity, devoid of any essentialism, is a legible, embodied performance of a cultural rhetoric that is regionally and temporally contextual. Orlando Cruz, a young gay Puerto Rican male boxer whose recent declaration of his sexuality made headlines, is the focus of this article. My assessment of the hypermasculine sport of boxing is informed by pugilistic history and an analysis of literary representation. I offer a more complex account of the cultural forces that shape Latino masculinity today by using boxing as a site of inquiry and combining the approaches of critical race theory and queer theory under the auspices of Jennifer Domingo Rudolph'smasculatinidad . I begin with the tragic events of the historic 1962 Griffith vs. Paret bout, and then move to a close reading ofBlade to the Heat, a play inspired by these events. I argue that Cruz succeeds in short-circuiting the dominant masculinity/sexuality binary that is assumed of Latino men and male athletes.